Analysis of Titania Nanosheet Adsorption Behavior Using a Quartz Crystal Microbalance Sensor - Yuichiro Tashiro; Satoshi Komasa; Akiko Miyake; Hiroshi Nishizaki; Joji Okazaki (Advances in Materials Science and Engineering)
We investigated the adsorption of albumin and fibronectin on a titania nanosheet- (TNS-) modified quartz crystal microbalance (QCM) sensor. A Ti QCM sensor was fabricated by reactive magnetron sputtering. A thin layer of Ti was deposited on the QCM sensor. This sensor was then alkali-modified by treatment with NaOH at room temperature to fabricate the titania nanosheets. Scanning probe microscopy, X-ray photoelectron spectroscopy, and scanning electron microscopy were performed to investigate the surface topology and chemical components of each sensor. The TNS had a titanium oxide film exhibiting a nodular structure and a thickness of 13 nm on the QCM sensor. Furthermore, QCM measurements showed significantly greater amounts of albumin and fibronectin adsorbed on the TNS than on titanium. The NaOH treatment of titanium modified the sensor surface and improved the adsorption behaviors of proteins related to the initial adhesion of bone marrow cells. Therefore, we concluded that TNS improves the initial adhesion between the implant materials and the surrounding tissues.